Global meta-analysis shows pervasive phosphorus limitation of aboveground plant production in natural terrestrial ecosystems - Enqing Hou (Nature Portfolio, 2020)
Plants are thought to be limited by phosphorus (P) especially in tropical regions. Here, Hou et al. report a meta-analysis of P fertilization experiments to show widespread P limitation on plant growth across terrestrial ecosystems modulated by climate, ecosystem properties, and fertilization regimes